Analisis Tingkat Sedimentasi Dan Gerusan Waduk PLTA Koto Panjang Bagian Hulu Menggunakan Data Penginderaan Jauh - Jailani, Jailani; Sutikno, Sigit; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Sedimentation and erosion in reservoir are common natural phenomena. Reservoir sedimentation and erosion caused by several factors such as: water level fluctuations in the reservoir and run off when it rains. Observation of reservoir sedimentation and erosion are done using remote sensing data. The data used are Landsat satellite imagery Landsat 7 ETM+ and Landsat 8 OLI_TIRS. Overview of sedimentation and erosion in this study conducted in 3 water level conditions. Based on the analysis results obtained: (1) condition 1 (mean water level 76,67 m), of date 1 September 2000 to 11 July 2013 (12,87 years) has occurred sedimentation and erosion, for 140,62 ha and 97,47 ha respectively, the rate of sedimentation and erosion, for 10,95 ha/year and 7,58 ha/year respectively. (2) the condition 2 (mean water level 77,73 m), of dates 9 December 2001 to 16 November 2013 (11,95 years) has occurred sedimentation and erosion, for 146,23 ha and 125,06 ha respectively, the rate of sedimentation and erosion, for 12,24 ha/year and 10,47 ha/year respectively. (3) Condition 3 (mean water level 79,75 m), of date 9 March 2000 to 18 December 2013 (13,79 years) has occurred sedimentation and erosion, for 325,69 ha and 73,23 ha respectively, the rate of sedimentation and erosion, for 23,62 ha/year and 5,31 ha/year respectively.Keywords : sedimentation , erosion , reservoir, remote sensing , Landsat